Health professionals' perspectives on the impact of COVID-19 on sexual and gender-based violence (SGBV) and SGBV services in Rohingya refugee communities in Bangladesh - Shahanoor Akter Chowdhury; Thomas McHale; Lindsey Green; Ranit Mishori; Chloe Pan; Isabel Fredricks (BMC, 2022)
Abstract Background The COVID-19 pandemic has acutely affected Rohingya refugees living in camps in Cox's Bazar, Bangladesh. Reported increases in sexual and gender-based violence (SGBV) were attributed in part to pandemic-related public health measures. In addition, the Government of Bangladesh's restrictions to prevent the spread of COVID-19 have impacted the provision of comprehensive care for survivors of sexual violence. This study sought to understand how the COVID-19 pandemic affected SGBV and the provision of services for Rohingya survivors in Bangladesh. Methods Interviews were conducted with 13 professionals who provided or managed health care or related services for Rohingya refugees after the onset of the COVID-19 pandemic in March 2020. Results At the outset of the COVID-19 pandemic, organizations observed an increase in the incidences of SGBV. However, health care workers noted that the overall number of survivors formally reporting or accessing services decreased. The pandemic produced multiple challenges that affected health workers' ability to provide essential care and services to Rohingya survivors, including access to the camps, initial designation of SGBV-related services as non-essential, communications and telehealth, difficulty maintaining confidentiality, and donor pressure. Some emerging best practices were also reported, including engaging Rohingya volunteers to continue services and adapting programming modalities and content to the COVID-19 context. Conclusions Comprehensive SGBV services being deemed non-essential by the Government of Bangladesh was a key barrier to providing services to Rohingya survivors. Government restrictions adversely affected the ability of service providers to ensure that comprehensive SGBV care and services were available and accessible. The Government of Bangladesh has not been alone in struggling to balance the needs of displaced populations with the necessary precautions to prevent the spread of COVID-19 and its response can provide lessons to others overseeing the provision of services during epidemics and pandemics in other humanitarian settings. The designation of comprehensive services for survivors of SGBV as essential is vital and should be done early in establishing disease prevention and mitigation strategies.